Amnesia and the Nation History, Forgetting, and James Joyce - Cheng, Vincent J. (New Directions in Irish and Irish American Literature, 2018)
This book examines the relationships between memory, history, and national identity through an interdisciplinary analysis of James Joyce's works-as well as of literary texts by Kundera, Ford, Fitzgerald, and Walker Percy. Drawing on thinkers such as Nietzsche, Marx, Freud, Luria, Anderson, and Yerushalmi, this study explores the burden of the past and the "nightmare of history" in Ireland and in the American South-from the Battle of the Boyne to the Good Friday Agreement, from the Civil War to the 2015 Mother Emanuel killings.